Identification of Islamic leadership principles and their applicability in construction project management - Ahmad Sarkawi, Azila; Abdul Rashid, Khairuddin; Aripin, Srazali; Hasan, Sharina Farihah; Mohd Fauzi, Puteri Nur Farah Naadia; Senam, Mohd Rosdi (University of Lagos, Nigeria, 2016)
Islamic leadership principles are universal in nature. They are applicable in all branches of human activities including in construction project management. However, current theories and practices in construction project management seldom focus on aspects related to religion and faith; whereas in dealings with human aspects, religion and faith are inseparable. Consequently, there is a need to bring the aspects of religion and faith into the practices of construction project management. This paper reports on a study that attempts to bring religion and faith into the contemporary practice of construction project management. In this context, the aspects on religion and faith are represented by incorporating Islam and its principles on leadership. Through extensive literature review and interviews with Islamic experts a list of Islamic leadership principles has been developed. The developed leadership principles are then assessed on their applicability in construction project management through face to face interviews with project managers currently serving the Malaysian Public Works Department. The findings from the study suggest that Islamic leadership principles are relevant, appropriate and highly applicable to be practised in construction project management. In addition, the project managers interviewed believe that by incorporating Islamic leadership principles into construction project management the probability of achieving the desired project outcome is significantly enhanced. Furthermore, to the Muslim project managers the practice of bringing in Islamic leadership principles into practice in construction project management would significantly enhanced the fulfilment of their religious obligations and strengthen their Islamic faith.